Physicochemical and antifungal properties of pyroligneous acid derived from macadamia nutshell (Macadamia integrifolia) and its application - Chaisang, Tamang; Sartoru, Kondo; Matchima, Naradisorn (Agriculture and Natural Resources, 2024)
Importance of the work: Macadamia nutshell (MNS) can be used as a bio-based fungicide, offering a natural alternative to synthetic chemicals and reducing waste. Objectives: Determine physicochemical properties and antifungal activities of pyroligneous acid (PA) from MNS, compare refinement methods and assess mango preservation efficacy. Materials and Methods: Macadamia nutshells were pyrolyzed at 600700°C to extract pyroligneous acid PA, which was then distilled, purified, and analyzed for yield, specific gravity, tar, solids, color, volatile compounds, and antioxidant activity. PA’s antifungal activity was assessed in vitro and on mangoes to evaluate its effectiveness in disease control and fruit quality. Results: Distillation-refined PA from macadamia nutshell demonstrated superior properties over naturally-refined PA, with an 87.55% yield, lower tar content (0.16%), and higher antioxidant activity. It had a lower pH (2.33), higher phenolic content (138.7 g GAE/L), and reduced total soluble solids (3.70% Brix). In-vitro analysis showed an effective antifungal activity against tested fungi with complete inhibition of Colletotrichum gloeosporioides and Colletotrichum musae at 1.5%. Combining 1.5% PA with 1% chitosan significantly enhanced the postharvest quality of Nam Dok Mai Sithong mangoes, reducing decay and weight loss while maintaining firmness, indicating a synergistic effect in preserving fruit quality. Main finding: Our study shows that distillation-refined MNS PA, exhibited a strong antioxidant and antimicrobial properties. PA at 1.5% conc. effectively inhibited Colletotrichum spp., and improved postharvest quality of ‘Nam Dok Mai Sithong’ mangoes, highlighting its potential use as an eco-friendly biocide.